PENGARUH DOSIS PUPUK ORGANIK CAIR DAN MACAMTANAH TERHADAP PERTUMBUHANAWAL MAHKOTA DEWA (Phalleria macrocorpa) - K. Dwi Catur Oktrianti; Rejeki Agustinah; Teguh Supryadi (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta)
The research are aimed to: (1) Analyze the dosage effect of liquid organic manure to growth early crown deity plant mahkota dewa; (2) Analyze the effect of soil kind to growth early crown deity plant mahkota dewa; (3) Anlyze the interaction between dosage effect of liquid organic manure with to growth early crown deity plant mahkota dewa, has been carried out on April 11, 2006 until July 20, 2006 in The Village of Klodran Colomadu Karanganyar, Central Java of 200 meters above the sea levels. The method research uses factorial method with Based Completely Randomized design (CRD) which of two distinguished treatment factors: (1) Liquid organic manure’s dosage (D0 = control, D1 = 6 g/plant, D2 = 8 g/plant, D3 = 10 g/plant) and (2) Kinds of soil (M1 = Alfisol, M2 = Entisol, M3 = Vertisol). The result shows: (1) The effect of liquid organic manure’s dosage does have significant effect on the number of leaves, the fresh weight of biomass, the dry weight of biomass as well as the root volume and diameter of stem but no significant effect on the height of plant; (2) The treatment of soil kind does have significant effect root volume, diameter of stem as well as the fresh weight of biomass but no significant effect on the height of plant; (3) The interaction of the two both treatment does have no significant effect on all of plant parameter; (4) The highest result on each parameter showed in the combination D3M2; 10 g/plant and entisol soil.